The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3233/wor-172534
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation model of interactions between risk factors and work-related musculoskeletal complaints among Iranian hospital nurses

Abstract: Structural equation modeling may provide methodological opportunities in occupational health research with a potential to explain the complexity of interactions among risk factors. Prevention of work-related musculoskeletal disorders among nurses must account for physical and psychosocial conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
4
14
0
1
Order By: Relevance
“…Individual factors such as age, gender, tenure, anthropometric parameters, personal habits, etc. seem to pose risks for LBP [18,19]. The most commonly reported biomechanical risk factors with at least reasonable evidence for causing LBP include excessive repetition and awkward postures [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Individual factors such as age, gender, tenure, anthropometric parameters, personal habits, etc. seem to pose risks for LBP [18,19]. The most commonly reported biomechanical risk factors with at least reasonable evidence for causing LBP include excessive repetition and awkward postures [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Office workers spend up to two-thirds of their working hours in sedentary postures [2]. This has negative effects on their health because they spend most of their wake time at work [3,4]. Musculoskeletal disorders (MSDs) present various symptom episodes and can happen in workers for many causes like excessive repetitions, high biomechanical and psychosocial demands, heavy lifting and social habits [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This has negative effects on their health because they spend most of their wake time at work [3,4]. Musculoskeletal disorders (MSDs) present various symptom episodes and can happen in workers for many causes like excessive repetitions, high biomechanical and psychosocial demands, heavy lifting and social habits [4,5]. MSDs manifest as pain and malfunction of the body structures and tissues; they are sometimes called repetitive strain injuries, and have a significant effect on the economy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still numerous amounts of challenges in understanding the association between musculoskeletal symptoms and various individual and occupational risk factors. Therefore, a cross-sectional study was carried out by Mehralizadeh, Dehdashti, and Kashani (2017) in Iran to examine the direct and indirect interactions of various risk factors with musculoskeletal complaints in hospital nurses. The study findings showed there was a personal effect of psychological, role-related, and work posture stressors on musculoskeletal complaints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study findings showed there was a personal effect of psychological, role-related, and work posture stressors on musculoskeletal complaints. 30 On the other hand, WMSD is a significant concern for public health, leading to temporary and permanent disability, and health care workers, including nurses, are at high risk for these disorders. Heidari, Borujeni, and Khosravizad (2018) conducted another crosssectional study among 300 nurses working in the teaching hospitals affiliated with Shiraz University of Medical Sciences (SUMS) to assess the health-promoting lifestyles of nurses and their association with musculoskeletal disorders and symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%